Mengintegrasikan Teknologi IoT dan Smart Destinations dalam Pengelolaan Pariwisata Berkelanjutan - Agung Yuliyanto Nugroho; Sri Yulianto Fajar Pradapa; Ferat Kristanto; Syah Riza Octavy Sandy (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The integration of Internet of Things (IoT) technology with the concept of Smart Destinations offers an innovative solution in tourism management with the aim of improving operational efficiency and tourist experience. IoT technology, which includes interconnected sensor devices and communication systems, provides the ability to unify and manage various aspects of a destination in real-time. Meanwhile, Smart Destinations use digital technology to optimize the tourist experience through personalization, resource efficiency, and desire. This article discusses the background and key benefits of IoT integration in Smart Destinations, including improving the visitor experience through data and analytics, better crisis management, and more efficient resource management. Application examples such as smart parking systems, automated energy management, and providing contextual information to tourists through sensors are described to illustrate the practical application of this technology. However, challenges such as data privacy and security, technology compatibility issues, and significant investment requirements are also discussed. In conclusion, while this integration faces several obstacles, its potential benefits in improving the quality and efficiency of tourist destinations make it a promising approach for the future of the tourism industry.